Cognitive failures in response to emotional contagion: Their effects on workplace accidents. (April 2019) - Petitta, Laura; Probst, Tahira M.; Ghezzi, Valerio; Barbaranelli, Claudio
Highlights: The interplay between contagion of emotions and cognitive failures is key to prevent workplace accidents. Lapses in cognitive functioning may be prevented by positive emotions that employees absorb during social interactions at work. Contagion of anger among employees enhances their cognitive failures and subsequent accidents. Abstract: The purpose of this study was to examine contagion of positive and negative emotions among employees as an antecedent of cognitive failures and subsequent workplace accidents. Using emotional contagion theory and the neural model of emotion and cognition, we tested the proposition that higher contagion of anger (i.e., a negative emotion accompanied by dysfunctional cognition) would be associated with greater cognitive failures, whereas higher contagion of joy (i.e., a positive emotion accompanied by pleasant information processing, attention and positive cognition) would be associated with fewer cognitive failures. In turn, cognitive failures were predicted to be related to higher rates of subsequent workplace accidents. Using a two-wave lagged design, anonymous survey data collected from N = 390 working adults in the U.S. supported the hypothesized mediation model. Specifically, emotional contagion of anger positively predicted cognitive failures, whereas emotional contagion of joy negatively predicted cognitive failures. Furthermore, cognitive failures positively predicted experienced accidents and fully mediated the relationship between contagion of joy/anger and experienced accidents. These findings suggest that lapses in cognitive functioning may be prevented by positive emotions (and enhanced by negative emotions) that employees absorb during social interactions at work and represent a more proximal source of accidents in comparison to emotions. Theoretical and practical implications of these results are discussed in light of the globally rising rates of workplace accidents and related costs for safety.